Koleksi Mushaf Kuno Museum Sejarah Al-Qur’an: Bukti Material Dinamika Islamisasi di Sumatera Utara - Lumbantoruan, Sarah bella; Perangin-Angin , Daniel Firdaus; Wahyudi; Eva Damanik (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research examines the collection of ancient manuscripts at the North Sumatra Museum of the History of the Qur'an as authentic material evidence of the process of Islamization in the region. Using qualitative methods through observation and historiographical studies, the study explores the physical characteristics and decorative motifs of the manuscripts, which represent local cultural identity. The findings indicate that the diversity of the manuscript collection attests to the existence of intellectual activity and a well-established tradition of Qur'an copying in North Sumatra since ancient times. Analysis of these artifacts confirms that the spread of Islam occurred through dynamic cultural acculturation, while also emphasizing North Sumatra's strategic position in the history of Islamic literacy in the Indonesian archipelago.